(untitled) (Eurasian Journal of Research, Development and Innovation, 2022)
The article deals with the fact that in the development of agriculture in Uzbekistan, priority attention is paid to the cluster system, which is widely implemented in the cotton and grain industries, to a much lesser extent in the fruit and vegetable industry, as well as strengthening the role of clusters, introducing new mechanisms of cooperation, financing producers of fruit and vegetable products and expanding the provision of agricultural services, which form the basis of a new systems of development of the fruit and vegetable industry of Uzbekistan